EVALUASI PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA KELURAHAN TANJUNG RHU KOTA PEKANBARU - Parasian Manurung; Zaili Rusli; Dadang Mashur (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This research is to find out and analyze the evaluation results of the community empowerment program based on the pillars of the community (PMB-RW) in the Tanjung Rhu Village and the inhibiting factors for the evaluation of the PMB-RW program in the Tanjung Rhu Village. This study uses a qualitative research method with a case study approach that is descriptive in nature through the process of collecting interview data, observation, and document study. The results showed that the evaluation of the PMB-RW program had not been carried out properly and maximally and that PMB-RW had not been able to handle and reduce the poverty rate in Tanjung Rhu Village. Evaluation of the context of the PMB-RW program has not been in accordance with the plan, has not been able to analyze the background of the implementation of PMB-RW and difficulties in achieving goals. Evaluation of the input of the PMB-RW program has not been able to utilize existing resources and the identification of resources has not been maximized.